1976
DOI: 10.2134/jeq1976.00472425000500040035x
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Fate of Three Dichlorophenyl Nitrophenyl Ether Herbicides in a Rice Paddy Model Ecosystem

Abstract: The distribution and fate of three 14C radiolabeled diphenyl ether herbicides, nitrofen (2,4‐dichlorophenyl 4′‐nitrophenyl ether), X‐52 or methoxy‐nitrofen (2,4‐dichlorophenyl 3′‐methoxy‐4′‐nitrophenyl ether), and bifenox (2,4‐dichlorophenyl 3′‐carbomethoxy‐4′‐nitrophenyl ether), were evaluated in a laboratory rice (Oryza sativa L., Taichung Native No. 1) paddy model ecosystem. Nitrofen was relatively stable under model ecosystem conditions and was bioconcentrated and stored over a 33‐day period in tissues of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Glutathione conjugation was observed in the metabolism of isoproturon (118), an aquatic macrophyte, whose metabolites were identified by LC-MS (Pietsch et al 2006). In addition to the usual cleavage of C-O and C-N bonds in esters and amides, a unique cleavage is known for the ether linkage in diphenyl ethers (Cai et al 2007(Cai et al , 2008Lee et al 1976), the S-N bond of bentazone (137) (Booth et al 1973), and the Sn-C bond of tributyltin (16) (Lee et al 1989;Maguire et al 1984).…”
Section: Other Pesticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione conjugation was observed in the metabolism of isoproturon (118), an aquatic macrophyte, whose metabolites were identified by LC-MS (Pietsch et al 2006). In addition to the usual cleavage of C-O and C-N bonds in esters and amides, a unique cleavage is known for the ether linkage in diphenyl ethers (Cai et al 2007(Cai et al , 2008Lee et al 1976), the S-N bond of bentazone (137) (Booth et al 1973), and the Sn-C bond of tributyltin (16) (Lee et al 1989;Maguire et al 1984).…”
Section: Other Pesticidesmentioning
confidence: 99%
“…A radiolabeled pesticide may be applied to any compartment of an ecosystem (such as water or bottom sediment) to simulate spray drift or a runoff event, etc. Aquatic model ecosystems can be classified as being terrestrial-aquatic (Metcalf et al 1971;Metcalf and Sanborn 1975), aquatic (Isensee 1976;Schuth et al 1974), and/or recirculating static (Ambrosi et al 1978;Isensee et al 1976Isensee et al , 1979a, and sitespecific models have been developed that emulate river (Lynch et al 1982;Maki and Johnson 1977;Rose and McIntire 1970) or paddy field (Chen et al 1982;Lee et al 1976;Wang et al 1992a) conditions. In Table 14 a long list of substances is presented that have been studied in model systems of one design or another.…”
Section: Model Ecosystemsmentioning
confidence: 99%
“…4. Whole body radioautograms offish exposed to 14C-CNP Radioautograms, a and b show the accumulation of 14C-CNP and its metabolites in viscera and intervertebral cartilage, respectively Lee et al (1976) also studied that distribution and fate of three diphenylether herbicides in a rice paddy model ecosystem. They found that nitrofen was relatively stable under model ecosystem conditions, and obtained the ecological magnification coefficient in Gambusia of 1546 for nitrofen, 867 for methoxy nitrofen and 49 for bifenox.…”
Section: Distribution Of Cnp and Its Metabolites In Fish Bodymentioning
confidence: 99%
“…The model ecosystem technique for the evaluation of pesticide biodegradability and ecological magnification was introduced in 1971 ( Metcalf and Kapoor 1971). Since then, several modified ecosystems were constructed to fit actual paddy field conditions (Chen, 1982 ;Lee, 1976).…”
Section: Introductionmentioning
confidence: 99%